Factors Influencing Consumer Decision to Buy Sport Bicycles: Understanding the Influence of Marketing Mix on Consumer Decision to Buy Sport Bicycles (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study had four major purposes (1) to determine the important level of marketing mix, (2) to determine the process of decision to buy sport bicycle, and (3) correlation between consumer decision to buy sport bicycle with the important level of marketing mix. This was quantitative research using questionnaire as a tool to collect data from 400 cyclists who ride sport bicycles in Bangkok and this study adopted measures included percentage, mean, standard deviation, t-test, one-way Anova, Pearson correlation, and multiple regression analysis.The results of the study showed that most of respondents were males, aged 31-40 years and older, were single and married, were bachelor degree holders, worked for private industries, and earned a monthly income of 20,001-30,000 baht. The average overall picture of the opinions on marketing mix factors were at high level and the process on consumer decision making on buying sport bicycles were at high level also. The hypothesis testing results on the different personal behavior patterns, such as gender, age, and marital status affected the process of consumer decision on buying sport bicycles and factors on marketing mix correlated to the process of consumer decision on buying sport bicycles were at high level in the same direction. The marketing mix factors, such as prices, distribution channel, marketing promotion influenced consumer decision on buying sport bicycles at statistically significant 0.05.Recommendations from the study results were that sport bicycles venders should offer a variety of sport bicycles with famous brand names, all sizes, modern design with good quality, warrantees, service after sales, appropriate prices per quality of bicycles, clearly prices tags, easy access bicycle shops, marketing promotion with free gift after purchased, advertising thru multimedia channels, and knowledgeable sale person to assist on selecting the right bicycle for exercises.